The 9th International Conference as part of a series of Na Tak conventions held in Poznan entitled: “Care, Therapy, Education – Subjectivity of People with Multiple Disabilities” Poznan, 29th November 2019 - Korach, Paulina (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
.